2023
DOI: 10.1186/s12903-023-03110-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of bioactive restorative materials in controlling secondary caries: a systematic review and network meta-analysis

Abstract: Background This systematic review and network meta-analysis aimed to compare the clinical efficacy of bioactive and conventional restorative materials in controlling secondary caries (SC) and to provide a classification of these materials according to their effectiveness. Methods A search was performed in Pubmed, Web of Science, Embase, BBO, Lilacs, Cochrane Library, Scopus, IBECS and gray literature. Clinical trials were included, with no language… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
(145 reference statements)
0
0
0
Order By: Relevance
“…The margins of restorations can be considered critical areas due to the possible presence of spaces or gaps produced by polymerization contraction, porosity, or fractures. Under these circumstances, biofilm accumulation is facilitated, which increases the degradation of restorations and can lead to the formation of caries lesions [ 74 ]. Furthermore, secondary caries is influenced by several factors, the most common being lesion location, patient’s caries risk, age and socioeconomic status, variation in operator skills, and detection methods and criteria [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The margins of restorations can be considered critical areas due to the possible presence of spaces or gaps produced by polymerization contraction, porosity, or fractures. Under these circumstances, biofilm accumulation is facilitated, which increases the degradation of restorations and can lead to the formation of caries lesions [ 74 ]. Furthermore, secondary caries is influenced by several factors, the most common being lesion location, patient’s caries risk, age and socioeconomic status, variation in operator skills, and detection methods and criteria [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in people at high risk of dental caries, a frequent decrease in pH is observed, which requires additional sources of ions, such as fluoride, to effectively contribute to the control of the DEM–REM process, as found in IRRs [ 79 ]. In another review, this parameter was shown to be more effective in glass ionomers and their derivatives, due to the lack of homogeneity in the included studies [ 74 ].…”
Section: Discussionmentioning
confidence: 99%